Effect of glycerol on the behaviour of an expansive soil during wetting and drying cycles. Issue 10 (24th August 2021) - Estabragh, A. R.; Babaei, M.; Javadi, A. A.
ABSTRACT: The behaviour of expansive soil with different flooding fluid, i.e. distilled water and solution of glycerol with different percentages of glycerol (10%, 20%, 30% and 40%) was studied through a number of cyclic wetting and drying tests. Experimental tests were conducted on compacted samples of the expansive soil in a modified oedometer with different flooding fluids under a surcharge pressure of 10 kPa. The vertical and radial deformations of the samples were determined during different stages of wetting and drying. The results showed that during cycles of wetting and drying, the deformation of the soil decreased with increasing the number of cycles for all flooding fluids. The magnitude of deformation for samples flooded with a solution of glycerol is less than distilled water and this reduction is a function of glycerol concentration. The equilibrium condition of samples with glycerol solution is reached in fewer cycles than distilled water. The results also indicated that the swelling-shrinking deformation was nearly the same when the equilibrium condition was attained. Comparison of the results showed that by increasing the percent of glycerol, these curves were contracted. Furthermore, the paths of wetting and drying converged to an S-shaped curve at equilibrium condition.